PENGARUH GREEN PERCEIVED VALUE DAN GREEN PERCEIVED QUALITY TERHADAP GREEN SATISFACTION DAN GREEN TRUST - Putra, Ketut Donny Surya; Rastini, Ni Made (E-Jurnal Manajemen, 2017)
The purpose of this study to determine the effect of green perceived value and green perceved quality of the green satisfaction and the green trust of The Face Shop products in Badung Regency. The samples used were 100 peoples and collected through non-probability sampling method. Data were collected by distributing questionnaires and using Likert scale. The analysis technique used is PLS. The analysis showed green perceived value influence positively and significantly to the green satisfaction and green trust. Green perceived quality affect positively and significantly to green satisfaction and green trust, and green satisfaction influence positively and significantly to the green trust. It is recommended that The Face Shop Management continuously strives to improve the positive value of the environment, providing additional quality in order to increase the satisfaction and trust of consumers.
Keywords: green perceived value; green perceived quality; green satisfaction; green trust